(untitled) (Journal of Forest and Livelihood, 2009)
p>In Nepal, the poor-focused Leasehold Forestry Programme (LHFP) is taken as an important programme to halt forest degradation and address poverty. This paper aims to analyse the policies and practices of the LHFP and identify lessons with regard to when, how and under what conditions the programme can benefit the poorer sections of the community. Our analysis shows that provisioning pro-poor forest policies has served as a good starter towards poverty reduction, but several dimensions need to be considered to maximise benefits and services for poor households. Such dimensions include: appropriate implementation mechanisms are instituted and local institutions promoted; community-level deliberations take place to maximise benefits for the poor; good condition forests are handed over to the poor to enhance their access to forest-based products; the programme works with multiple programmes and partners to address poverty on a fuller scale to go beyond the current level of involvement of few development sectors. Key words: leasehold forestry, pro-poor, poverty reduction Full text is available at the ForestAction website Journal of Forest and Livelihood 6(2) September 2007 pp.20-29